2011
DOI: 10.1002/j.0022-0337.2011.75.12.tb05217.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Academic Performance for Applicants to an International Dental Studies Program in the United States

Abstract: The number of U.S. and Canadian dental schools offering programs for dentists with degrees from other countries leading to the D.D.S. or D.M.D. degree has increased recently. This fact, along with the diversity of educational systems represented by candidates for these programs, increases the importance of identifying valid admissions predictors of success in international dental student programs. Data from 148 students accepted into the international dental studies program at the University of the Pacific fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Instead, foreign-trained dentists were obliged to apply and successfully complete a 2- or 3-year dental educational program in order to become licensed practitioners. These changes were introduced in order to protect the public and ensure that international dentists were adequately trained to meet U.S. standards [ 9 , 10 , 11 ]. Presently, licensing requirements for foreign-trained dentists in the U.S. are strict, confusing, complex and are conferred by individual state licensing boards.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, foreign-trained dentists were obliged to apply and successfully complete a 2- or 3-year dental educational program in order to become licensed practitioners. These changes were introduced in order to protect the public and ensure that international dentists were adequately trained to meet U.S. standards [ 9 , 10 , 11 ]. Presently, licensing requirements for foreign-trained dentists in the U.S. are strict, confusing, complex and are conferred by individual state licensing boards.…”
Section: Introductionmentioning
confidence: 99%
“…This model enables the proper assessment of the skills development process in a practical setting by correlating variables such as the age of the students, previous experience, etc. [11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the criteria for admission into the IDS program at the University of the Pacific Arthur A. Dugoni School of Dentistry, they concluded that the Test of English as a Foreign Language (TOEFL) and NBDE Part I exams had a strong influence in evaluating foreign–trained dental applicants for their program. Since English is the language of instruction in the United States, it is important for a foreign–trained dentist to be proficient in that language to be able to seek admission into this type of program 12 …”
mentioning
confidence: 99%